Metode Design Thinking pada Aplikasi Pembelajaran Berbasis Audio untuk Mahasiswa Disabilitas Netra - Rasapta, Diki (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Visually impaired students often face challenges in accessing text- and visual-based learning materials, particularly in Management Information Systems (MIS) courses, which heavily rely on diagrams and tables. This study aims to develop an audio-based learning application as a more accessible alternative, focusing on enhancing students’ understanding of MIS content. The application was developed using the Design Thinking approach, which includes five stages: empathize, define, ideate, prototype, and test. Visually impaired students were directly involved in the design and testing process to ensure the application meets their specific needs. The results indicate that the developed application significantly improves students' comprehension, with an average post-test score increase of 32% compared to the pre-test (from 58 to 90). Moreover, the use of audio-based technology enhances independent learning, reduces reliance on external assistance, and provides a more inclusive learning experience. The effectiveness of the Design Thinking approach is reflected in a user satisfaction rate of 92%, demonstrating that this method successfully delivered a relevant and adaptive solution. This study is expected to serve as a reference for the development of more inclusive learning technologies for students with special needs, particularly those with visual impairments.